The ionization parameter of star-forming galaxies evolves with the specific star formation rate - Kaasinen, Melanie; Kewley, Lisa; Bian, Fuyan; Groves, Brent; Kashino, Daichi; Silverman, John; Kartaltepe, Jeyhan (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. We investigate the evolution of the ionization parameter of star-forming galaxies using a high-redshift (z∼ 1.5) sample from the FMOS-COSMOS (Fibre M